Trabectedin may be a valuable treatment option for elderly patients with metastatic soft tissue sarcomas - Miolo, Gianmaria; Buonadonna, Angela; Lombardi, Davide; Scalone, Simona; Lauretta, Andrea; Della Puppa, Lara; Corona, Giuseppe (Frontiers in Oncology, 2024)
Background: In the landscape of metastatic soft tissue sarcomas (mSTS) treatment, anthracyclines have shown efficacy; however, their associated toxicity imposes significant limitations, especially in frail elderly mSTS patients who are highly susceptible to severe adverse effects. In this context, trabectedin, due to its distinct pharmacological profile and safety profile may represent an interesting alternative being demonstrated active in treating mSTS. These features hold particular significance for elderly and unfit mSTS patients, where the balancing treatment benefits with potential adverse effects represents the pivotal objective.The investigation was focused on specific group of 11 elderly mSTS patients aged ≥70, all undergoing first-line treatment with trabectedin and it was supported by comprehensive pharmacokinetic and pharmacodynamic studies. Among these patients, 9 out of 11 started the treatment at the dose of 1.5 mg/m2.The primary objective of this investigation is to highlight trabectedin as a valuable first-line treatment option for elderly and unfit mSTS patients. Additionally, this investigation seeks to explore whether higher administered doses of trabectedin can enhance clinical outcomes while maintaining the same toxicity profiles. The median Progression-Free Survival (PFS) was 77 days (95% CI, 53-89), the median overall survival (OS) was 397 days (95% CI, 66-2102) while the overall toxicity of grade 3-4 severity amounted to 43%.These findings provide new insights into the clinical outcomes and toxicity associated with trabectedin in elderly patient population, enhancing our understanding of better treatment approaches for specific population of mSTS patients.